PELUANG DAN TANTANGAN PERBANKAN S Y ARI AH DI INDONESIA - Priyono . (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2002)
Monetary crisis that start in Indonesia on second quarter of 1997 still have a great impact, even now. And now, the crisis start to spread to another sector of human life and become multidimensional crisis; economic and financial, politics, social and even mental crisis. In this case, people become veiy critical from time to time. They see the injustice and hoping for another kind of economic system that is more righteous and more content. That system is only avaliable based on syariah banking system that use split interest rate. The government to the people needs for the birth of the new economic system that bring more justice. Therefore in 1992, the government approved UU No. 71992, that give chance to operate split interest banks. Hereafter, the government in 1998 regularizes UU No. 10 / 1998 that is an addendum to previous UU no. 7/1992. The Point of that regulation is that the Indonesian Bank (Central Bank) acknowledged the syariah banks as well as conventional banks. To give more brief pointers and guidance, Bank Indonesia also published blue print of developing Indonesia’s syariah banking system. With the steps above, hopefully chances and challenges that arise can be managed perfectly so the hope of economics system and syariah banking system that based on equality will reach its purpose Perdagangan saham yang bertujuan mendapatkan keuntungan antara pemilik modal dengan emiten merupakan hal baru yang belum pemah dikenal baik pada masa Rasulullah, para sahabat maupun tabiin. Hal ini tentu akan menarik jika dikaji bagaimana hukum perdagangan saham dalam perspektif Islam ? Inilah yang akan dibahas dalam tulisan ini